Classical Distributive Justice and the European Healthcare System: Rethinking the Foundations of European Health Care in an Age of Crises. Issue 2 (30th January 2015) - Bauzon, Stéphane
Abstract: The state subvention and distribution of health care not only jeopardize the financial sustainability of the state, but also restrict without a conclusive rational basis the freedom of patients to decide how much health care and of what quality is worth what price. The dominant biopolitics of European health care supports a healthcare monopoly in the hands of the state and the medical profession, which health care should be (re)opened to the patient's authority to deal directly for better basic health care. In a world where it is impossible for all to receive equal access to the best of basic health care, one must critically examine the plausible scope of the authority of the state to limit access to better basic health care. Classical distributive justice affords a basis for re-examining the current European ideology of equality, human dignity, and solidarity that supports healthcare systems with unsustainable egalitarian concerns.